Pertanggungjawaban Pidana Terhadap Penyalahgunaan Kecerdasan Buatan (Artificial Intelligence) dalam Tindak Kejahatan Digital di Indonesia - Yoel Bessoran (Ikatan Da'i Indonesia, 2026)
This study analyzes the phenomenon of artificial intelligence based digital crime in Indonesia during the period 2023 to 2026, with a focus on deepfake, voice cloning, digital fraud, and the misuse of autonomous algorithms. The study employs a normative juridical approach combined with empirical case analysis to evaluate criminal liability mechanisms, challenges in legal implementation, as well as the roles of corporations and end users in the dissemination of harmful digital content. The results show that artificial intelligence functions as a mediator of complex crimes, therefore existing regulations, including the Criminal Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law, are not yet adequate to effectively enforce criminal liability. The phenomena of non consensual deepfake, voice phishing, and image manipulation create legal gaps that require regulatory reform and adaptive models of legal responsibility. This study emphasizes the importance of combining individual and corporate liability, the application of risk based liability and vicarious liability principles, as well as internal supervision and risk mitigation among AI platform developers. In addition, cross institutional coordination, integration of digital forensic technology, and public education are key to successful investigation and law enforcement. These findings provide implications for national policy reform, strengthening corporate ethical standards, and strategies to prevent the misuse of artificial intelligence, while also highlighting the urgency of adapting legal frameworks to continuously evolving digital technologies. Therefore, this study contributes to the development of a more comprehensive legal and policy framework to address artificial intelligence based digital crime in Indonesia.